A Case of Disulfiram-Induced Psychosis in a Previously Asymptomatic Patient Maintained on Mixed Amphetamine Salts: A Review of the Literature and Possible Pathophysiological Explanations. Issue 5 (September 2016) - Spiegel, David R.; McCroskey, Aidan; Puaa, Kapaakea; Meeker, Grant; Hartman, Lauren; Hudson, Joshua; Hung, Yu C.
Abstract : Abstract: Although perhaps better known as an irreversible aldehyde dehydrogenase inhibitor causing increased acetaldehyde levels after concomitant intake of ethanol, disulfiram or one of its metabolites (diethyldithiocarbamate) also inhibit dopamine β-hydroxylase, an enzyme that converts dopamine to norepinephrine. This mechanism has been advanced as a possible explanation for the development of psychosis, during disulfiram treatment, either in monotherapy or in combination therapy, when interaction-emergent psychosis could be causal. We present a young woman who was taking mixed amphetamine salts for treatment of attention-deficit/hyperactivity disorder and developed a short-lived psychosis after introduction of disulfiram. The psychotic symptoms resolved after discontinuation of both medications, without the use of antipsychotic drugs. We proceed with a review of the literature of disulfiram-induced psychosis and discuss pathophysiological theories that possibly were involved in our patient's phenomenology.